Polysporangiate anthers described in Eugenia (Myrtaceae) with notes on evolutionary patterns - Giaretta, Augusto; Souza, Maria Anália D.; Amorim, Bruno S.; Sano, Paulo T.; Lucas, Eve (Phytotaxa, 2024)
Shifts towards compartmentalisation resulting in multilocular anthers have been described in some families of Myrtales but to date, not in Myrtaceae. In these other families sporogeneous tissue is partitioned by transverse or longitudinal septa, fitting the definition of the ‘polysporangiate anther’. Polysporangiate anther in Eugenia, a Neotropical genus of Myrtaceae is here discussed, with a detailed description of their morphology and in the context of known phylogenetic relationships within Eugenia. Anthers of Eugenia joseramosii, E. kerianthera and E. petaloidea were examined using scanning electron microscopy; E. multilocellata and E. quilombola were imaged with light microscope. Molecular sequences of five regions were used to place these species in a representative phylogenetic framework for character reconstruction analysis. Analysed anthers share dithecal organization in which each anther theca is divided in dorsal and ventral rows of sporangia. Polysporangiate anthers in Eugenia appear to have evolved independently on at least two occasions in Eugenia sect. Umbellatae. Eugenia flowers with polysporangiate anthers fit a generalist pollination pattern but Eugenia petaloidea demonstrates some unusual features that may be linked to pollination by vibration. Anthers in Eugenia is a rare condition with low systematic value. Resources should be invested to survey Myrtaceae for more species with polysporangiate anthers, to improve understanding of their evolutionary relevance and to record pollinators and modes of pollination.